Study on the Viable but Non-culturable (VBNC) State Formation of Staphylococcus aureus and Its Control in Food System - Li, Yanmei; Huang, Teng-Yi; Mao, Yuzhu; Chen, Yanni; Shi, Fan; Peng, Ruixin; Chen, Jinxuan; Yuan, Lei; Bai, Caiying; Chen, Ling; Wang, Kan; Liu, Junyan (Frontiers in Microbiology, 2020)
A Viable but non-culturable (VBNC) state is a bacterial survival strategy under reverse conditions. It poses a significant challenge for public health and food safety. In this study, the effect of external environmental conditions including acid, nutrition, and salt concentrations on the formation of S. aureus VBNC states at low temperatures were investigated. Different acidity and nutritional conditions were then applied to food products to control the VBNC state formation. Four different concentration levels of each factor (acid, nutrition, and salt) were selected in a total of 16 experimental groups. Nutrition showed the highest influence on the VBNC state formation S. aureus, followed by acid and salt. The addition of 1% acetic acid could directly kill S. aureus cells and inhibit the formation of the VBNC state with a nutrition concentration of 25, 50, and 100%. A propidium monoazide-polymerase chain reaction (PMA-PCR) assay was applied and considered as a rapid and sensitive method to detect S. aureus in VBNC state with the detection limit of 104 CFU/mL.